Modelling R&D and Innovation Support Systems – Analysis of Regional Cluster Structures in Innovation in Portugal - Teresa de Noronha Vaz; Purificación Vicente Galindo; Peter Nijkamp (Tinbergen Institute, 2013)
This paper offers a new methodology to identify R&D and innovation clusters, on the basis of a regional analysis of innovation support systems in Portugal. Using a web-based inventory of R&D and innovation agencies, an extensive data base is created. This data set is next analyzed by means of Principal Coordinates Analysis followed by a Logistic Biplot approach (leading to Voronoi mappings) in order to design a systematic typology of innovation clusters in the main regions in Portugal. A striking result is the significant difference in innovation systems at regional level in Portugal. The paper is concluded with policy recommendations.
Keywords: Q55; Q16; 330; R&D and innovation; regional innovation systems; principal coordinates analysis; logistic biplot; Voronoi mapping; public policy